ANALISIS YURIDIS TENTANG PASAL 1057 KUHPERDATA SEBAGAI DASAR DALAM MENGAJUKAN PERMOHONAN PENOLAKAN HAK ATAS WARIS DI PENGADILAN NEGERI - Avriantara, Fally (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Article 1057 of the Civil Code mandates that the provisions for denial of inheritance rights must be stated expressly at the Registrar's Office of the District Court in whose jurisdiction the inheritance is open. However, there is no clearer or firmer explanation regarding what is meant by the phrase "open legal areas for inheritance." There are those who interpret it as the last domicile where the testator lived and/or died, but there are some who think it is the domicile of the applicant. This research aims to analyze article 1057 of the Civil Code as a basis for submitting a request for denial of inheritance rights in the district court. This research is juridical-normative research with the legal sources used in this research consisting of: (1) primary legal materials in the form of the Civil Code and Court Decisions and (2) secondary legal materials in the form of scientific works discussing civil law and inheritance law. The author obtained the results that practice in the field in several Court Decisions shows that rejection of an inheritance must occur firmly in the form of a written statement at the District Court clerk's office, in whose legal area the inheritance has been opened, namely the heir's last domicile of residence and death as stipulated in Article 1057 BW/Civil Code